Factors Influencing Emergency Department Utilization and Hospital Re-Admissions in a Predominantly Obese, Racially Diverse Urban Renal Transplant Population. (March 2021) - Lichvar, Alicia B.; Patel, Alisha; Pierce, Dana; Gimbar, Renee Petzel; Tzvetanov, Ivo; Benedetti, Enrico; Campara, Maya
Introduction: Early emergency department and hospital re-admissions are common in renal transplant recipients, but data are lacking in unique populations. Study Aim: The purpose of this study was to identify patient risk factors for multiple acute care utilization events within the first year of renal transplantation. Design: This was a single-center, retrospective cohort study of adult renal transplant recipients between 9/2013-9/2016. Patients were compared across number of emergency department visits and by hospital re-admissions. Diagnoses were categorized. Univariate and multivariate logistic regression was used to assess risk for multiple acute care utilization events within the first 12 months post-transplant. Results: A total of 216 patients were analyzed and were on average 50.5 (SD 13.9) years old, redominantly Black (49.77%) with an average body mass index of 33.33 (9.8) and were recipients of deceased donor renal transplants (61.11%). A total of 105 (48.6%) patients visited the emergency epartment and 119 (55.1%) patients had a hospital readmission. Patients having a body mass index >35 kg/m2 did not differ across emergency department visit or hospitalization groups. Delayed graft function (OR 2.86, 95% CI 1.07-7.65) and previous renal transplant (OR 2.77, 95% CI 1.04-7.39) were significantly associated with multiple acute care utilizations. Discussion: Acute care utilization following renal transplantation was similar to previously reported experiences. Obesity did not impact use of acute care resources or patient outcomes. Strategies addressing potential preventable emergency visits and hospital re-dmissions should be promoted.